Prevalence and visual outcome of glaucoma with uveitis in a Thai population - Kessara Pathanapitoon (2018)
© 2016 Wolters Kluwer Health, Inc. Objective: The aim of this study was to report on the prevalence of uveitic secondary glaucoma (USG) and ocular hypertension in patients with uveitis in Thailand, and to identify factors associated with the development of USG and its visual outcome. Design: This is a retrospective cohort study. Methods: We included 174 consecutive uveitis patients (237 affected eyes) visiting the Ophthalmology Department of Chiang Mai University Hospital, Thailand, from January 2013 to March 2013. Results: The prevalence of USG was 29% (51/174) and that of ocular hypertension was 18% (32/174). The follow-up period ranged from 3 to 96 months (mean±SD=33±21 mo). Characteristics associated with the development of USG were as follows: Age at onset of uveitis above 60 years and longer duration of uveitis (P=0.001). No association between location of uveitis and development of USG was observed. Clinical entities associated with the highest prevalence of USG consisted of Posner-Schlossman syndrome and herpetic uveitis. Within the anterior uveitis group, viral etiology was strongly associated with the development of USG, whereas human leukocyte antigen-B27 (HLA-B27)-associated anterior uveitis had lower prevalence of USG than did their HLA-B27-negative counterparts. The prevalence of patients with at least 1 blind eye was significantly higher in those who developed USG (21/51; 41%) than in uveitis patients without glaucoma (22/123; 18%, P=0.001). Characteristics associated with visual loss in USG included poor visual acuity at presentation (P<0.001), and undergoing glaucoma surgery (P<0.05). Conclusions: The prevalence of secondary glaucoma among Southeast Asian patients with uveitis was 29%. Blindness in at least 1 eye developed more commonly in patients with USG than in uveitis patients without USG.